1996
DOI: 10.1093/infdis/173.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of US Inactivated Split-Virus and Russian Live Attenuated, Cold-Adapted Trivalent Influenza Vaccines in Russian Schoolchildren

Abstract: In a blinded, placebo-controlled study, the reactogenicity, immunogenicity, and clinical efficacy of single doses of US inactivated split-virus and Russian live attenuated, cold-adapted influenza vaccines were compared in 555 schoolchildren in Vologda, Russia. Serial serum samples were collected and school absenteeism was assessed. Systemic reactions were rare, but local reactions (primarily erythema at the injection site) were observed in 27% of the inactivated vaccine group, and coryza (12%) and sore throat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 8 publications
2
29
0
3
Order By: Relevance
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…With EPI-Info, version 6 (CDC, Atlanta, GA, USA) we estimated that a minimal cohort size of 330 children would give us an 80 % chance of detecting a reduction of at least 50 % [15,27,28] in outcome events among recipients of the vaccine. We assumed for this calculation an immunization rate of 45 %, an event rate of 25 % in unvaccinated persons and a twosided alfa level of 5 %.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the cohort was large enough to demonstrate an expected 50 % reduction of outcomes resulting from the vaccine based on earlier observations. Sugaya et al [15], for example, recorded a 49 % reduction in febrile episodes in vaccinated asthmatic children aged 2-14 years, Khan et al [28] demonstrated a vaccine efficacy for preventing school absenteeism due to respiratory illness of 56 % in healthy children and Gross et al [27] recorded a 50 % reduction in influenza-related illness among the elderly in a large meta-analysis. In the 1996-7 season we were therefore able to demonstrate a statistically significant vaccine protectiveness of 56 % overall and of 77 % in the youngest asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…9,44,45 Infection rates in young children are comparable to or higher than in adults, 46 -48 and lost productivity as a result of influenza at all ages results in substantial costs to society. 14 Preschools are now an integral part of American life and (as with schools) increase the risk of infection for participating children and for secondary transmission to family members.…”
Section: Discussionmentioning
confidence: 99%